Bovine cumulus-granulosa cells contain biologically active retinoid receptors that can respond to retinoic acid - Malayer Jerry; Thirumalapura Nagaraja; Mohan Mahesh (BMC, 2003)
Abstract Retinoids, a class of compounds that include retinol and its metabolite, retinoic acid, are absolutely essential for ovarian steroid production, oocyte maturation, and early embryogenesis. Previous studies have detected high concentrations of retinol in bovine large follicles. Further, administration of retinol in vivo and supplementation of retinoic acid during in vitro maturation results in enhanced embryonic development. In the present study, we hypothesized that retinoids administered either in vivo previously or in vitro can exert receptor-mediated effects in cumulus-granulosa cells. Total RNA extracted from in vitro cultured cumulus-granulosa cells was subjected to reverse transcription polymerase chain reaction (RT-PCR) and mRNA expression for retinol binding protein (RBP), retinoic acid receptor alpha (RARalpha), retinoic acid receptor beta (RARbeta), retinoic acid receptor gamma (RARgamma), retinoid X receptor alpha (RXRalpha), retinoid X receptor beta (RXRbeta), retinaldehyde dehydrogenase-2 (RALDH-2), and peroxisome proliferator activated receptor gamma (PPARgamma). Transcripts were detected for RBP, RARalpha, RARgamma, RXRalpha, RXRbeta, RALDH-2, and PPARgamma. Expression of RARbeta was not detected in cumulus-granulosa cells. Using western blotting, immunoreactive RARalpha, and RXRbeta protein was also detected in bovine cumulus-granulosa cells. The biological activity of these endogenous retinoid receptors was tested using a transient reporter assay using the pAAV-MCS-betaRARE-Luc vector. Addition of 0.5 and 1 micro molar all-trans retinoic acid significantly (P < 0.05) increased the activity of the pAAV-MCS-betaRARE-Luc reporter compared to cells transfected with the control reporter lacking a retinoic acid response element. Addition of 5 or 10 micro molar all-trans retinol stimulated a mild increase in reporter activity, however, the increase was not statistically significant. Based on these results we conclude that cumulus cells contain endogenously active retinoid receptors and may also be competent to synthesize retinoic acid using the precursor, retinol. These results also indirectly provide evidence that retinoids administered either in vivo previously or in vitro may have exerted a receptor-mediated effect on cumulus-granulosa cells.